Development of a new method for maintainability and downtime analysis of mining machinery - M. Rezaei Dashtaki; A. Jandaghi Jafari; S. H. Hoseinie (Scientific Reports)
Abstract Shovels are universally acknowledged as vital machinery in surface mining production systems, and enhancements to this equipment substantially augment operational mine output capacity. Extending the length of continuous operation is a cost-efficient strategy that may result in significant productivity improvements, as it is directly linked to the fleet’s reliability and maintainability. This research analyses the maintainability of a fleet of ten rope shovels in an open-pit copper mine, consisting of three separate models. To this end, repair data for all ten shovels over two years were analyzed, and maintainability models were assigned to each shovel. The results indicate that all shovels are predominantly maintained in less than 45 h, and 80% of repairs can be accomplished within a single shift, which is operationally understandable and manageable for the entire crew. Alongside maintainability research, a novel quantitative method has been established to examine the composition of downtimes based on primary categories of action: pre-repair actions, repair actions, and post-repair actions. Analysis of 25 mechanical and 25 electrical failures revealed that repair duration was almost 50% of the overall downtime. The residual time was allocated to multiple tasks, including vehicle arrival, delays, requisite preparations, diagnostics, and performance testing and validation. Approximately 30% of the overall downtime stemmed from the duration needed for transportation from the repair facility to the machine and operational delays. The findings established a foundation for recommending a viable approach to enhance the maintenance and repair conditions of the Shovel fleet at the copper mine under consideration.